ANALISIS KINERJA KOMISI INFORMASI KABUPATEN CIREBON DALAM MENDORONG KETERBUKAAN INFORMASI PUBLIK - Desty Hidayati; Mukarto Siswoyo; Hery Nariyah (Universitas Swadaya Gunung Jati, 2020)
The establishment of the Information Commission is based on Law number 14 of 2008 on Public Information Disclosure which mandates the establishment of the Central Information Commission and Provincial Information Commission as well as the Municipal or District Information Commission if necessary. This research was conducted at the Cirebon District Information Commission. The purpose of this research is to know how the performance of information commission of Cirebon district in encouraging public information disclosure and what factors that can push and hinder the performance of information commission in encouraging public information disclosure and efforts what have been done. This research uses descriptive qualitative research method. Data collection procedures used with interviews, observation, documentation. Data analysis is done by data reduction, data presentation, and conclusion. Data validity is done with a degree of trust (triangulation). The results of research and analysis on the Performance of Cirebon District Information Commission using some indicators of research focus that researchers use, the conclusion that researchers pull is the performance performed by Cirebon District Information Commission is still not well proven from the public there are still many who do not know the existence of Information Commission and in the settlement, information disputes are still not optimal. as well as the factors that can push and obstruct the information disclosure arises from the internal itself is the scope of the secretariat of information commissions that must be improved so that the expected performance can be maximal again. Suggestions that can be given authors that until now there are many people who do not know the existence of information commissions, with conditions like this should be more informed commission information in conveying the purpose of information disclosure by conducting socialization activities to the community directly. The process of dispute resolution of information also needs to be improved by providing more maximal service again and improve existing resources, such as complementing facilities that can support the activities of the Cirebon District Information Commission.Keywords: Performance and Public Information Disclosure